Anthelmintic Activity Test of Young Areca Nut (Arecha catechu L.) Extract Against Fasciola sp. Worm Eggs in Goat Feces In Vivo - Siregar, Alzahra wulandari; Nurzainah Ginting; Ade Trisna (Jurnal Peternakan Integratif, 2024)
Worm infections in livestock can have a huge risk impact such as decrease in growth, body weight, meat quality and death. This study aims to determine the anthelmintic activity of young areca nut extract (Areca catechu L.) against Fasciola sp. worm eggs in goat feces in vivo and to determine at what concentration the young areca nut extract (Areca catechu L.) is effective in providing anthelmintic effects against worm eggs. The study used an experimental method with a paired t-test of 5 treatments and 4 replications. The treatments given were P0 (negative control), P1 (10% areca nut extract), P2 (20% areca nut extract), P3 (30% areca nut extract) and P4 (positive control using kalbazen worm medicine). Parameters were reduction in the number of dead worm eggs, lethal concentration, Â effectiveness of areca nut extract against worm eggs. The results of the study showed that there were Fasciola sp. worm eggs in all tested goats. Treatment with young areca nut extract (Arecha catechu L.) can significantly reduce the number of Fasciola sp. eggs (P <0.05), with an LC50 result of 26.75%. The best Fecal Egg Count Reduction Test (FECRT) result in the administration of areca nut extract with a concentration of 30% (P3) of 56.75% was the same as that given treatment using kalbazen worm medicine and the lowest FECRT result in the administration of areca nut extract with a concentration of 20% (P2) of 29%.